Scrotal Peritoneal Mesothelioma on PET/CT - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2014)
Although malignant mesothelioma originating from the tunica vaginalis has been reported in the literature, direct invasion of malignant peritoneal mesothelioma to the scrotal cavity has not been described yet. Herein, we presented a diffuse malignant peritoneal mesothelioma extending inferiorly to the scrotum via inguinal canal detected on FDG PET/CT.
Keywords: malignant mesothelioma; FDG; PET/CT; scrotum; peritoneum; MALIGNANT MESOTHELIOMA